Tuberculosis transmission from healthcare workers to patients and co-workers: a systematic literature review and meta-analysis. - Monica Sañé Schepisi; Giovanni Sotgiu; Silvia Contini; Vincenzo Puro; Giuseppe Ippolito; Enrico Girardi (PLoS ONE)
Healthcare workers (HCWs) are at risk of becoming infected with tuberculosis (TB), and potentially of being infectious themselves when they are ill. To assess the magnitude of healthcare-associated TB (HCA-TB) transmission from HCWs to patients and colleagues, we searched three electronic databases up to February 2014 to select primary studies on HCA-TB incidents in which a HCW was the index case and possibly exposed patients and co-workers were screened.We identified 34 studies out of 2,714 citations. In 29 individual investigations, active TB was diagnosed in 3/6,080 (0.05%) infants, 18/3,167 (0.57%) children, 1/3,600 (0.03%) adult patients and 0/2,407 HCWs. The quantitative analysis of 28 individual reports showed that combined proportions of active TB among exposed individuals were: 0.11% (95% CI 0.04-0.21) for infants, 0.38% (95% CI 0.01-1.60) for children, 0.09% (95% CI 0.02-0.22) for adults and 0.00% (95% CI 0.00-0.38) for HCWs. Combined proportions of individuals who acquired TB infection were: 0.57% (95% CI 7.28E-03 - 2.02) for infants, 0.9% (95% CI 0.40-1.60) for children, 4.32% (95% CI 1.43-8.67) for adults and 2.62% (95% CI 1.05-4.88) for HCWs. The risk of TB transmission from HCWs appears to be lower than that recorded in other settings or in the healthcare setting when the index case is not a HCW. To provide a firm evidence base for the screening strategies, more and better information is needed on the infectivity of the source cases, the actual exposure level of screened contacts, and the environmental characteristics of the healthcare setting.